Law No. 14 of the Year 2013 On Allowing The Minister Of Finance To Guarantee The Egyptian Electricity Holding Company And Its Subsidiaries In Respect Of The Finance Obtained Thereby, And To Ensure The Settlement Of Their Financial Obligations Regarding The Projects Contracted For Thereby And Executed Through Or In Participation With The Private Sector = قانون رقم 14 لسنة 2013 فى شأن الإذن لوزير المالية بضمان الشركة القابضة لكهرباء مصر وشركاتها التابعة فيما تحصل عليه من تمويلات وضمان الوفاء بالالتزامات المالية فيما تتعاقد عليه من مشروعات يتم تنفيذها من خلال القطاع الخاص أو بالمشاركة مع القطاع الخاص - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.